1962
DOI: 10.3181/00379727-110-27577
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Formation of Deoxycholic and Lithocholic Acid by Human Intestinal Microorganisms.

Abstract: 552ACID AND HUMAN INTESTINAL MICROORGANISMS hyaluronic acid did not occur until the 2nd and 3rd hour following intravenous injection. Only traces of intravenously injected hyaluronic acid appeared in the synovial space, skin or vitreous humor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The significance of the 'H-labeled compounds with the mobility of cholylglycine is unknown. According to available evidence, neither chenodeoxycholic nor deoxycholic acid is hydroxylated in the liver of man (19)(20)(21), and if rehydroxylation occurred in our studies its magnitude was small; 7-rehydroxylation of deoxycholic acid does occur in the liver of several other species (22)(23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…The significance of the 'H-labeled compounds with the mobility of cholylglycine is unknown. According to available evidence, neither chenodeoxycholic nor deoxycholic acid is hydroxylated in the liver of man (19)(20)(21), and if rehydroxylation occurred in our studies its magnitude was small; 7-rehydroxylation of deoxycholic acid does occur in the liver of several other species (22)(23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…These authors have further demonstrated that although nonconjugated cholic acid acts weakly to enhance esterification, deoxycholate, a bacterial product of cholic acid (16,17), is inhibitory. They have suggested that bacterial alteration of bile acid structure in the blind loop syndrome could lead to impaired fat absorption.…”
Section: Discussionmentioning
confidence: 99%
“…According to published data, daily fecal excretion of bile acids varies from 87 mg (cholic acid metabolites only) to 2114 mg, depending on the methods of measurement used, and on the regimen given to the patient under study (23). If the average daily excretion of bile acids is assumed to be of 500 mg in an average adult, of this amount about 200 mg is deoxycholic acid and 300 mg is nonabsorbable lithocholic acid (24). Then, in the context of the present study.…”
Section: Discussionmentioning
confidence: 99%